Tata Kelola Lingkungan yang Baik dalam Implementasi Peraturan Daerah Nomor 1 Tahun 2018 tentang Pengelolaan Sampah di Kabupaten Aceh Tengah - Kuhini, Finta; ashwad, hajar; Teniro, Alwin; Efendi, Muhsin; tiara, rismi (Saraq Opat: Jurnal Administrasi Publik, 2026)
In 2023, waste production in Kabupaten Aceh Tengah reached approximately ±40 tonnes per day. The existing final disposal sites (TPA) are currently overloaded and can no longer optimally accommodate the volume of waste. Waste production has increased significantly from year to year. In 2025, the daily volume of waste is projected to reach 70.5 tonnes, originating from urban activities, particularly in the sub-districts of Bebesen, Lut Tawar, Kebayakan, and Pegasing, with a total population of 103,742. This situation indicates serious pressure on the regional waste management system. In response to this problem, the Central Aceh Regency Government enacted Central Aceh Regency Qanun No. 1 No 2018 concerning Waste Management as the legal basis for systematic and sustainable waste management. This study aims to examine the implementation of the Qanun, focusing on the role of the Environment Agency (DLH) as the policy implementer, the obstacles encountered in its implementation, and the factors that support the success of the implementation. The problem of waste management in Aceh Tengah Regency is still quite complex. This is characterised by limited facilities and infrastructure, particularly landfill capacity that has exceeded its capacity, a limited fleet of waste transport vehicles, and low levels of public awareness and participation in sorting and disposing of waste in accordance with regulations. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the implementation of Qanun No. 1 of 2018 still faces various significant obstacles, especially in terms of limited facilities and low community participation. However, there are supporting factors that strengthen the implementation of the policy, namely the existence of clear regulations, the commitment of the DLH as the implementing agency, the beginning of community participation, and the support of regional political legitimacy. Overall, the implementation of waste management policies in Central Aceh Regency is still in the development stage. In the future, it will be necessary to strengthen waste infrastructure, increase budget allocations, provide continuous education to the community, and develop circular economy-based strategies so that waste can be managed as a resource with economic value.